An in-vitro evaluation of three types of drug-eluting microspheres loaded with irinotecan - Pereira, Philippe L.; Sommer, Christof-Matthias (Anti-cancer drugs, 2016)
To compare the mechanical and chemical properties of three commercially available microspheres loaded with irinotecan. LifePearl (200 µm), DC Bead (100-300 µm), and Tandem (100 µm) microspheres were loaded with irinotecan. For loading, elution, and stability determinations, irinotecan concentrations were quantified using validated high-performance liquid chromatography methods. In-vitro elution was performed over 24 h using a USP 4 dissolution apparatus. Diameter measurements were performed using light microscopy. Time in suspension was considered as the time required for the microspheres to vacate 1/3 of the volume. All three microsphere types rapidly loaded irinotecan, with more than 95% loading at 1 h. In-vitro elution of irinotecan was rapid for LifePearl and DC Bead microspheres, with more than 98% elution at 1 h, and delayed for Tandem microspheres, with about 70% elution at 6 h. After loading with irinotecan, the average diameter of LifePearl and DC Bead microspheres was reduced by 9 and 18%, respectively, and was unchanged for Tandem microspheres. All three microsphere types lost 4-6% of the loaded irinotecan almost immediately upon placement in contrast: water and contrast: 5% dextrose, but further losses were minimal over 2 weeks. LifePearl microspheres remained longer in suspension (392±23 s) compared with DC Bead (154±13 s, P<0.001) and Tandem (198±19 s, P<0.001) microspheres. All three microsphere types load irinotecan rapidly. LifePearl and DC Bead microspheres elute irinotecan rapidly. Elution is delayed with Tandem microspheres. LifePearl microspheres show the longest time in suspension.